FOSTERING SUSTAINABLE DEVELOPMENT IN EDUCATION: ADDRESSING PRACTICES AND PERSPECTIVES FOR THE TWENTY-FIRST CENTURY - Jagneet, Kaur; Raino, Bhatia (INTI International University, 2023)
The importance of education in fostering practices that contribute to sustainable development is examined in this study. Educating towards Sustainable Development, or ESD, has made significant progress in gaining recognition from worldwide commissions and organizations during the past few decades. In 2004, the United Nations proclaimed that the period from 2005 to2014 would be the Decade of Education for Sustainable Development. To equip people with the information necessary to maintain sustainability in their communities and nations, it is notadequate to rely exclusively on the formal education system, which only has an impact on individualsfor a finite amount of time. Fortunately, ESD goes beyond what istaught in traditional schools and requires coordination in between both the formal and informal educational sectors. These sectors include nature centers, non-governmental organisations, educators in public health, and agricultural extension agents. In addition, educating people about the need of sustainability is a task that never ends. In the best case scenario, these several sectors would work together to promote ESD to the broader public by concentrating their efforts on certain groups of people and problems that are relevant to sustainability. On a worldwide basis, there is a growing consensus that education for sustainable development (ESD) is an essential ingredient in good educational practise. It is important to note that ESD has been incorporated into both the Muscat Agreement and the 2030 Agenda for Sustainable Development, both of which are associated with the Global Education for All Meeting. The purpose of this study is to investigate the relationships that exist among human development, ESD, sustainable development, and the Sustainable Development Goals (also known as SDGs). It highlights the significance of ESD in the global education debate and emphasises the relationship between education and the attainment of all of the Sustainable Development Goals (SDGs), with aparticular focus on ESD.